MENINGKATKAN PRESTASI BELAJAR MATEMATIKA MELALUI METODE LATIHAN - Munawaroh Munawaroh (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2015)
The study was aimed to (1) describe the mathematic learning process angle measurement through training method and (2) describe an increase the learning outcome of mathematics angle measurement through training method. The study was conducted at the fourth graders of the state elementary school Pandanpancur, Deket, Lamongan, which is designed with the approach of classroom action research (PTK) in two cycles. Each cycle was done through four stages: planning, implementation, observation and reflection. The results showed that the students’ learning outcome was 67.31, it was quite high compared with pre-cycle was 56.89. In the second cycle, the average of formative score was 87.86 for students has prepared their selves, be open, and understood the concept of angle measurement. These results recommended that the training method can improve students' learning achievement.